Meteorological data from Šibenik, Croatia, August 2020 - Mariana Ribas-Ribas; Ander López-Puertas; Oliver Wurl; Sanja Frka (PANGAEA, 2025)
Meteorological data recorded every 5 minutes during the August 2020 Šibenik campaign. Measurements were taken with an on-site weather station located near the sampling area.
In: Ribas-Ribas, M et al. (2025): Diel variability of thermohaline and carbon system parameters in the sea-surface microlayer and underlying water of a Mediterranean coastal site (Šibenik, Croatia) [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.984017